Graduates’ Unemployment and Entrepreneurship Quality in Tunisia - OMRI, Ibtissem (International Journal of English Literature and Social Sciences (IJELS), 2019)
This work seeks to verify the extent to which the socio-economic, cultural and political context influences the entrepreneurial intention of young Tunisian students. Particular attention is paid to the fact that the unemployment rate of tertiary graduates is strongly influencing the dynamism of entrepreneurship, especially in the "marginalized" regions. To do this, a questionnaire survey was conducted to better identify the main obstacles to entrepreneurial development. It has been clear that unemployment and the socio-economic inequalities separating the Tunisian regions have a strong influence on the adopted entrepreneurial strategy (Pull or Push strategy). This result is of paramount importance in that it explains in large part the blocking of the process of economic development in this country. The solution proposed was to call for the “visible hand” of the State in order to really realize a kind of bold entrepreneurial policy that can solve the socio-economic problems encountered by Tunisia.